Unraveling the Mechanism of the Singlet Oxygen Ene Reaction: Recent Computational and Experimental Approaches - Alberti, Mariza N.; Orfanopoulos, Michael (Chemistry : a European journal, 2010)
The mechanism of the singlet oxygen ene reaction has been a subject of renewed interest within the last few years. The main question being whether this reaction proceeds through a concerted mechanism or if it involves discrete intermediates. In general, the majority of experimental and computational studies support a traditional stepwise mechanism involving a perepoxide‐like intermediate. In this minireview we highlight the most prominent and recent theoretical, as well as experimental results relating to the challenging mechanism of the singlet oxygen ene oxyfunctionalization. Concerted or stepwise? Recently, the mechanism of the singlet oxygen ene reaction has been a subject of renewed interest, particularly, whether the reaction is concerted or involves discrete intermediates. The majority of experimental and computational studies support a traditional stepwise mechanism involving a perepoxide‐like intermediate (see scheme). This Minireview highlights some of the classical and most recent theoretical and experimental results relating to the mechanism of the 1O2 ene oxyfunctionalization.